(untitled) (Research, Society and Development, 2021)
Objective: To map the evidence regarding the functional impacts in patients affected by Covid-19 in severe form treated in the intensive care. Review method: This is a scoping review proposed by Joanna Brigges Intitute, filed and registered in the Open Science Framework (OSF) under the doi: https://doi.org/10.17605/OSF.IO/ESJYR . Studies published from March to December 2020 in the languages: English, Portuguese and Russian will be selected and reviewed, the database selected for search was LILACS, PEDro, MEDLINE / PUBMED and gray literature. Expected results: The mapping of the functional impacts of patients affected by COVID-19 and the actions of the physiotherapist, will bring enormous contributions from the point of view of evidence-based practices for the expansion of knowledge on the subject. Conclusion: It is hoped that the results expected from this study can contribute to the advancement of safe practices and qualities with the aim of restoring the functionality of the victims of COVID-19 as early as possible.